The Role of Employees' Well-being in Mediating the Effect of Job Stress and Job Insecurity on Performance Health Workers During the Covid-19 Pandemic: (Study on Health Workers of Anwar Medika Hospital-Sidoarjo) - Budi, Agus Setia; Mohyi, Achmad; Malik, Nazaruddin (University of Muhammadiyah Malang, 2023)
The research aimed to analyze and test the role of employees' well-being in mediating the effect of work stress and job insecurity on the performance of health workers at RSU Anwar Medika – Sidoarjo during the COVID-19 pandemic. Explanatory research is a type of research used with a quantitative approach and data collection methods using survey methods Types of research using explanatory research types survey methods by giving questionnaires to 187 health workers as respondents. The SEM-PLS method is used in data analysis and testing with the help of the SmartPLS 3 application program. The results of direct tests are known that work stress has an insignificant negative influence on the performance of health workers, job insecurity has a negative and significant effect on the performance of health workers, and employees' well-being has a positive and significant effect on the performance of health workers. Work stress has a negative and significant effect on employees' well-being, and job insecurity has a negative and significant effect. The results of indirect influence testing with the results that employees' well-being is unable to mediate the effect of work stress on the performance of health workers negatively and insignificantly, while the effect of job insecurity on the performance of health workers employees' well-being can mediate negatively and significantly.